Detection of physical helplessness at home using ambient sensor information - Storf, Holger; Jedlitschka, Andreas; Knaup-Gregori, Petra; Dickhaus, Hartmut (Journal of ambient intelligence and smart environments, 2014)
Societal changes lead to an increase in the number of critical emergency situations in single households, resulting in the need for new concepts, such as automatic detection of physical weakness. This paper describes an approach that identifies devia
Gesehen am 29.10.2020